High-purity amorphous silica from industrial filter cake waste: synthesis and process optimization - Ermias Abebe Negash; Belay Brehane Tesfamariam; Getinet Asrat Mengesha; Yonas Shasho; Yeabsira Sisay Mekuriya; Sena Tadesse Beyene (Materials Research Express)
The globally increasing concern over industrial byproducts highlights the need for sustainable waste management solutions. Repurposing such byproducts offers a promising approach to sustaining development. This study focuses on the extraction of silica from filter cake waste (FCW). Amorphous silica was successfully synthesized through sol–gel method using acetic acid as the precipitation agent. XRD and SEM analyses were used to confirm the crystal structure of silica to be amorphous, while FTIR studies identified characteristic Si−O−Si bonds, indicating high purity of the extract. The silica purity was further validated by EDS analysis to be about 98.98%. Optimization of the extraction process was carried through variation of parameters such as NaOH concentration, temperature, and stirring time, resulting in a maximum yield of 54%.